2010
DOI: 10.1136/thx.2009.125435
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a new once-daily long-acting inhaled  2-agonist indacaterol versus twice-daily formoterol in COPD

Abstract: Background Indacaterol is a long-acting inhaled b 2 -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
247
1
11

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 260 publications
(277 citation statements)
references
References 23 publications
18
247
1
11
Order By: Relevance
“…Comparable safety of these two treatments was also observed in the previous 6-month open-label comparison [2], and indacaterol has previously demonstrated an acceptable tolerability and safety profile with the 300 mg and the abovetherapeutic 600 mg doses given for up to 1 yr compared with placebo [12]. Overall, these results present a reassuring safety profile for this new bronchodilator.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Comparable safety of these two treatments was also observed in the previous 6-month open-label comparison [2], and indacaterol has previously demonstrated an acceptable tolerability and safety profile with the 300 mg and the abovetherapeutic 600 mg doses given for up to 1 yr compared with placebo [12]. Overall, these results present a reassuring safety profile for this new bronchodilator.…”
Section: Discussionsupporting
confidence: 64%
“…While potentially interesting, the actual differences of 30-40 mL are very small and well below the 100-140 mL level of clinical relevance [14]. Previously, indacaterol has been reported to have a similar effect in patients with differing COPD severities [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Dahl et al used indacaterol 150 mcg and formoterol 12 mcg for 1 year in COPD patient found indacaterol more efficacious. 6 Also MEHLER et al 7,8 showed that Overall ADR noticed over a period of 24 weeks were less and comparable in both groups. No SAE were reported.…”
Section: Discussionmentioning
confidence: 99%
“…Indacaterol has also demonstrated superior bronchodilation and clinical efficacy compared with the twice-daily LABAs salmeterol [66] and formoterol [67], and is at least as effective in improving lung function and symptoms as tiotropium [68,69].…”
Section: Indacaterolmentioning
confidence: 99%